2012
DOI: 10.1055/s-0032-1304646
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Glycogen Content in Ovariectomized Rats

Abstract: The aim of the present study was to investigate the effects of resistance training on glycogen content and muscle cross-sectional area (CSA) in ovariectomized rats. Wistar rats were divided into: sedentary; ovariectomized sedentary; resistance trained; and ovariectomized resistance trained. In the 12-week resistance training, the animals climbed a 1.1 m vertical ladder, 3 days per week, with 4-8 climbs. Cardiac, liver and muscle glycogen content was determined. After the 12-week resistance training period ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…These data were similar to those in our previous study . In OVX rodent models, hepatic glycogen contents were reported to decrease . Overnight fasting may induce further decrease in hepatic glycogen contents in OVX‐HFHC mice, and resulted in lower fasting serum glucose levels in this study.…”
Section: Resultssupporting
confidence: 92%
“…These data were similar to those in our previous study . In OVX rodent models, hepatic glycogen contents were reported to decrease . Overnight fasting may induce further decrease in hepatic glycogen contents in OVX‐HFHC mice, and resulted in lower fasting serum glucose levels in this study.…”
Section: Resultssupporting
confidence: 92%
“…The conversion of xanthine dehydrogenase (XD) into xanthine oxidase (XO) is among the mechanisms involved in the induction of oxidative damage in the liver during exercise. XO reduces O 2 instead of NADP + , thereby producing superoxide ions (O 2 • ) (4). Da Silva et al (36) investigated the effects of different physical exercise protocols on OS markers in murine livers and found that continuous running and downhill running for 45 min daily, 5 days/week for 8 weeks, decreased the lipid peroxidation levels, as assessed by TBARS.…”
Section: Discussionmentioning
confidence: 99%
“…Menopause (ovariectomy in animals) is associated with increased food intake and body weight, metabolic dysfunction, loss of bone mineral density, diabetes, impairment of muscle function, and increased inflammatory markers and oxidative stress (OS) (1-4). OS may result in lipid peroxidation of cell membranes, damage to proteins, and DNA and stellate cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Because the rats had to climb the ramp with a load attached to a steel cable connected to a plastic belt surrounding the animal's body, the eccentric component during the strength exercise was minimal, which may have led to a minor impact on muscle damage compared with the aerobic exercise protocol. Nevertheless, there are other resistance training protocols for rats that have the same limitation of the eccentric phase of the movement . We only assessed the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are other resistance training protocols for rats that have the same limitation of the eccentric phase of the movement. 29,30 We only assessed the gastrocnemius muscle. Thus, the results may have limited applicability to other muscles because of the predominance of type II muscle fibers.…”
Section: Discussionmentioning
confidence: 99%